Assisted delivery of anti-tumour platinum drugs using DNA-coiling gold nanoparticles bearing lumophores and intercalators: towards a new generation of multimodal nanocarriers with enhanced action. Issue 40 (23rd August 2019) - Caballero, Ana B.; Cardo, Lucia; Claire, Sunil; Craig, James S.; Hodges, Nikolas J.; Vladyka, Anton; Albrecht, Tim; Rochford, Luke A.; Pikramenou, Zoe; Hannon, Michael J.
Abstract : Nanocarriers with unusual DNA binding properties provide enhanced cytotoxic activity beyond that conferred by the platinum agents they release. Abstract : New gold and lipoic based nanocarriers for the delivery of platinum(ii ) and platinum(iv ) drugs are developed, which allow enhanced loading of the drug on the surface of the nanocarriers and release in a pH-dependent fashion, with superior release at lower pHs which are associated with many tumours. The conjugate nanoparticles and their conjugates enter cells rapidly (within 3 hours). They tend to cluster in vesicles and are also observed by light and electron microscopies in the cytoplasm, endoplasmic reticulum and nucleus. We further incorporate aminoanthraquinone units that are both fluorophores and DNA intercalators. This results in nanocarriers that after drug release will remain surface decorated with DNA-binders challenging the conventional design of the nanocarrier as an inert component. The outcome is nanocarriers that themselves have distinctive, remarkable and unusual DNA binding properties being able to bind and wrap DNA (despite their anionic charge) and provide enhanced cytotoxic activity beyond that conferred by the platinum agents they release. DNA coiling is usually associated with polycations which can disrupt cell membranes; anionic nanoparticles that can cause novel and dramatic effects on DNA may have fascinating potential for new approaches to in-cell nucleic acid recognition. Our findings have implications for the understanding and interpretation of the biological activities of nanoparticles used to deliver other DNA-binding drugs including clinical drug doxorubicin and its formulations.